Pengaruh Harga, Citra Merek, Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Sop Kambing Bang dudung di Cimone, Kota Tangerang(Studi kasus pembelian dalam gofood) - Putri, Asyifa (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
Abstract:This research aims to analyze the influence of the variables Price (X1), Brand Image (X2), Promotion (X3), and Product Quality (X4) on the decision to purchase Bang Dudung goat soup in Cimone, Tangerang City via GoFood. Using quantitative methods with 97 respondents and purposive sampling, this research analyzes data using multiple linear regression via IBM SPSS 20. The research results show that each independent variable has a significant influence on purchasing decisions. Based on the t test, the Price variable (T count = 4.048) has a significant influence with a significance value of 0.000 < 0.05. Brand Image (T count = 12,442), Promotion (T count = 4,709), and Product Quality (T count = 3,416) also show a significant influence with a significance value of 0.000 < 0.05. The simultaneous F test shows that the variables Price, Brand Image, Promotion and Product Quality together have a significant effect on Purchasing Decisions, with calculated F = 36.969 and a significance of 0.000 < 0.05. Thus, this research concludes that there is a positive and significant influence of all variables on the decision to purchase Bang Dudung Kambing Sop at GoFood.